DESAIN PENGEMBANGAN PEMBELAJARAN AKIDAH AKHLAK DI PERGURUAN TINGGI - Rofiah, Nurul Hidayati (FENOMENA, 2016)
Aqidah akhlak is one of the topics of Islamic education study program which is urgently and fundamentally importance since it explains and study the values of iman and akhlak. The values of iman and akhlak are fundamental values for student so that she/he could implement the appropriate good religious value and social value. The discussion of aqidah and akhlak becomes important in emerging the knowledge and understanding the iman, meanwhile at the same time the student enables to implement the iman values in his/her real life in the form of good akhlak. This is one of the urgencies of aqidah akhlak education which has a goal to collaborate the concept and the implementation of hablumminallah and hablum minannas fair and well. The pattern of the design and the development of aqidah akhlak teaching should be prepared and implemented well so that the teaching of it will be effective and efficient. By doing so, the goal of teaching will be achieved well.